BALISEERING GENEALOGY: DECONSTRUCTING THE DUCTH COLONIAL EDUCATION IN NORTH BALI AND ITS IMPLICATION IN GLOBALIZATION ERA - Pageh, I Made; Kumbara, A.A Ngurah Anom; Wirawan, A.A. Bagus; Sukardja, Putu (E-Journal of Cultural Studies, 2015)
Baliseering in education hides the motives of the colonial ideological interest which are inserted in various colonial policies; it is hegemonic in regard to its structure and culture and has widely affected North Bali. In this present study, the qualitative method was used. In other words, the data were collected through interview, observation, and library research. The data were analyzed using the genealogic concepts of knowledge, domination, and hegemony (Foucault, Gramsci, and Giddens). However, the data which were related to education were eclectically analyzed using the concepts proposed by Bourdieu, Paulo Freire, and Ivan Ilich. The result of the study shows that genealogically Baliseering in education hide the colonial ideology and interest which was inserted in various discourses of colonization and hegemony in the society’s structure and culture with its wide impact. The motivation of Baliseering was obtaining cheap human resources in the bureaucratic modernization and making Bali an exotic tourist destination. The structure and culture of the Balinese people were created in a dominative and hegemonic way through hegemonic and colonial concepts in the traditional villages ‘Desa Pakraman’ in Bali. Its implication was highly wide; the political structure had been made to be hegemonic. In addition, ethnocentrism, primordialism, and colonization had been made to appear in both formal and informal education, causing liberalism and internationalism to appear. Apart from that, education had been made to be marginalized for the poor.
Keywords: Baliseering, ideology, colonization, critical education